2021
DOI: 10.1177/00469580211025211
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life among Blood Cancer Patients in Pakistan: A Cross Sectional Survey

Abstract: The importance of health-related quality of life and its determinants including physical, emotional, and functional domains has long been recognized among blood cancer patients in the developed world but this concept is still in infancy in developing countries, including Pakistan. The objective of the study was to assess health related quality of life among blood cancer patients. A descriptive cross-sectional study design was used. A pre-validated questionnaire that is EORTC-QLQ-C30 was self-administered to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Our Global QOL score was found to be comparable to international studies on GI cancer patients ranging from (55-76.8) [19][20][21][22]. When we compared our global QOL score with other studies on Pakistani population, we observe a better score in our GI cancer patients as compared to patients with blood cancer (25.95), breast cancer (48.33) and with different combination of cancer on chemotherapy (57.37) [9][10][11]. These differences can be explained by complete different spectrum of symptomatology, treatment options especially chemotherapeutic drugs and problems associated with those treatment modalities.…”
Section: Discussionsupporting
confidence: 77%
“…Our Global QOL score was found to be comparable to international studies on GI cancer patients ranging from (55-76.8) [19][20][21][22]. When we compared our global QOL score with other studies on Pakistani population, we observe a better score in our GI cancer patients as compared to patients with blood cancer (25.95), breast cancer (48.33) and with different combination of cancer on chemotherapy (57.37) [9][10][11]. These differences can be explained by complete different spectrum of symptomatology, treatment options especially chemotherapeutic drugs and problems associated with those treatment modalities.…”
Section: Discussionsupporting
confidence: 77%
“…This study showed that, while financial difficulty had the highest average score among symptom scales, three symptoms were higher than the others; fatigue, insomnia, pain. Malik et al (2021) reported that the symptoms with the highest scores were insomnia, dyspnea, and diarrhea in the blood cancer patients group. AlFayyad et al ( 2020) reported that anorexia is a statistically significant predictor of clinically significant fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Pashos et al (2013) stated that in the CLL patient group, males had a better FACT-Leu total score than females. Malik et al (2021) highlighted relatively better HRQoL among female blood cancer patients. Pashos et al (2013) reported worse physical scores and fatigue scores in females than males in the CLL patient group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations